Dampak DER Dan ROE Terhadap Return Saham Indeks LQ45 - Pradiasty, Dwi Ayu; Juwita, Ratna (Universitas Multi Data Palembang, 2024)
This research aims to see the effect of DER and ROE on Stock Returns on the LQ45 index on the IDX. The sample used was 15 issuers on the LQ45 index on the IDX using a purposive sampling method. This research concludes that DER not significantly on Stock Returns, while ROE a significantly on stock returns.